ANALISIS TERHADAP KESINAMBUNGAN LEMBAGA PEMBIAYAAN PEDESAAN DALAM MENDUKUNG USAHA MIKRO, KECIL DAN MENENGAH - Khusnul Ashar (Journal of Indonesian Applied Economics, 2011)
The research goal is to find how far the degree of sustainability of rural financialinstitutions that exist and to identify the variables that determine what operationalsustainability yaginstitutions concerned. From the results of statistical tests and thediscussion can be summarized as follows: The degree offinancial sustainability forrural finance institutions significantly affected by the variable operating cost andrevenue variables which level income has a positive relationship while variable costshave a negative relationship. The influence of variable operating costs are relativelygreater than the influence of income variable; Good Rate Revenues and Cost ofOperations has a positive relationship and the real magnitude of value of receivables/loan value; level offinancial sustainability of institutions did not show a clear patternof relationship with the efficiency (either from the indicator value of loans per staffand per-unit cost of borrowing/Cost per unit of Money Lent); Compared with theindicator Cost per unit of Money Lent, the value of loans per staff show a clearerpattern of relationship with the magnitude of the Average-Performing Asset (the Costper unit of Money Lent did not show a clear pattern of relationship with the Average-Performing Asset). Average value addition is dominated by the Performing AssetValue Receivable. It can be concluded that the greater the value of Average Perform-ing Assets, the greater the value of receivables and the more efficient institutions KSP.Keywords: financial institutions, sustainability